Engineering Design and Prototyping of an Automated Shuttlecock Feeder with Programmable Court-Zone Targeting - P. E. Punithan; R. Ramakrishnan; G. Nallavan; K. Jayanarasimhan (Three E Science Institute, 2026)
Manual multi-shuttle badminton drills can introduce variability in feeding rate and placement, reducing training standardization and complicating objective evaluation. Automated, programmable feeding with zone-based metrics can address this limitation. To design and validate a low-cost, automatic nine-shot shuttlecock feeder that delivers shuttlecocks to predefined court zones with controllable speed, direction, and timing. The prototype combined a wooden frame with 3D-printed dropper/ejector components and a dual-wheel launcher fixed at 30°. An ESP32 coordinated two DC motors (launch wheels) and three servomotors (dropper, ejector, and horizontal aiming). Nine-shot programs targeted a 3×3 court grid (left/center/right × front/mid/rear). The feeder was mounted 1.10 m above an indoor regulation court and 1.30 m from the net. For each zone, 12 feather shuttlecocks were launched (108 trials). Dual-camera video (60–120 fps) captured trajectory and top-view landings; Dartfish tagging and planar-homograph calibration converted pixel coordinates to court distances (mean spatial error <3%). All nine programs were executed successfully and produced distinct zone-specific landing distributions. Landing-distance variability was low (coefficient of variation <12% across programs), indicating strong repeatability under fixed settings; rear-court programs showed longer mean distances with similarly tight dispersion. Feeding reliability was 100% across 108 launches, with no blocking, double-feeding, or missed shots. Flight time and estimated near-field launch speed changed consistently with the programmed motor settings. The proposed feeder enables repeatable, structured multi-shuttle training and provides a practical framework for quantifying zone-delivery performance, with future work directed toward refining closed-loop targeting.